Biomechanical services for top level swimming - Mason, B. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The Australian Institute of Sport (A.I.S.) was establishe in 1981 as a consequence of Australia`s poor performance at the 1976 Olympic Games. Swimming is Australia`s premier Olympic sport as the national swim team wins more Olympic medals for Australia than any other sport. This paper will focus upon A.I.S. Biomechanical services for elite competitive swimming in Australia. DEVELOPMENT During the first 5 years of the A.I.S., only very basic qualitative servicing was provided for all sports. The next 5 years saw the development of more sport specific servicing, together with small research projects. Following the first 10 years of A.I.S. development saw more research aimed toward developing sports specific analysis systems in the biomechanics of swimming. Such systems as the large analysis system for competition meets were developed, the portable SWAN competition analysis system for individual swimmer analysis in meets and the SWAN start and turn analysis system for the training environment eventuated. In 2006 the Aquatics Testing, Training and Research Unit (A.T.T.R.U) was established along with a new 50m technology pool. With the new pool came the development of the Wetplate analysis system designed to analyse starts, turns and relay changeovers, and the active drag system. RESEARCH Because of the new Wetplate and Active drag analysis systems providing more quantitative information about performance, fundamental research could now be used to solve problems raised by the swim coaches. Research associated with Wetplate included projects linked with optimising the performance off the new kick plate starting blocks, optimising knee bend and extension in turns to generate maximum force off the wall and deciding the placement of the newly permitted dolphin kick in breaststroke starts and turns. Research associated with drag analysis included the generation of video associated with the propulsive force generated by the swimmer to identify stroke inefficiencies. A method has also been established to compute active drag over a range of swim velocities from passive drag values over set velocities and the active drag at the swimmer`s maximum velocity. Computational fluid dynamics is also being researched as a possible way to investigated what would eventuate with instigating changes in technique before actually altering the swimmer`s technique.